THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, FIRM SIZE, AND NET PROFIT MARGIN ON COMPANY VALUE (Study on Fast Moving Consumer Goods Company (FMCG) In 2016-2020) - Rafi Raihan Wahid (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The purpose of this study was to examine the effect of Current Ratio, Debt to Equity Ratio, Firm Size, and Net Profit Margin on firm value (Tobin's Q) in the food and beverages sub-sector listed on the Indonesian stock exchange in the 2016-2020 period. The phenomenon that is the main focus in this study is the decline in the average company stock price on the Jakarta Consumer Index (JKCONS) in the last 5 years which is inversely proportional to the growth in total assets and company profits in the food and beverages sub-sector which increased. The population in this study amounted to 87 companies. The sampling technique used purposive sampling, total sample is 23 companies. The analysis technique uses the Multiple Regression analysis method and the classical assumption is tested first. The results of the analysis in this study is: Current Ratio has insignificant effect on firm value, debt to equity ratio has positive and significant effect on firm value, firm size has negative and significant effect, and net profit margin has insignificant effect. This research is expected to contribute to the development of the science of Financial Management, especially in research on Company Value (Tobin's Q).